Persepsi Aparatur Sipil Negara Di Sekretariat Daerah Kabupaten Kepulauan Sangihe Tentang Efektivitas Implementasi Work From Home - Katarina Bataha; Sumainah Fauziah (Jurnal Penelitian Administrasi Publik, 2020)
This article aims to determine the perceptions of state civil servants at the Regional Secretariat of the Sangihe Islands Regency on the implementation of work from home and how the effectiveness of the implementation of work from home. The hope is that this article can become a policy recommendation for the government in formulating policies related to the implementation of work from home in the future as an anticipatory step considering the changing environment. The method used in writing this article is a qualitative method with a descriptive approach. The data collection technique was carried out through interviews with six state civil servants at the Regional Secretariat of Sangihe Islands Regency who were determined purposively. The effectiveness of the implementation of work from home referred to in this article is viewed from the support of infrastructure and performance achievements. The results show that the implementation of work from home depends on an electronic communication system based on information technology. During work from home, public services continue to run effectively at the Regional Secretariat of Sangihe Islands Regency. There are even new lessons that are useful for improving state civil servants skills. Keywords: ; Effectiveness, Implementation, Work From Home